Flood‐plain responses to contemporary climate change in small High‐Arctic basins (Svalbard, Norway). (9th January 2014) - Owczarek, Piotr; Nawrot, Adam; Migała, Krzysztof; Malik, Ireneusz; Korabiewski, Bartosz
<x xml:space="preserve">Abstract</x> Changes in the supply of water and sediment to high‐latitude rivers related to contemporary climate change and glacier fluctuations largely determine the activity of fluvial processes. This study reconstructs fluvial dynamics since the end of the Little Ice Age (LIA) in two small, partially glaciated basins in the southern part of Spitsbergen, Svalbard Archipelago. We use a combination of aerial photograph interpretation, field mapping and dendrochronological analysis. Sequences of abandoned channels and glacifluvial terraces are distinctly visible in middle and lower parts of the Brattegg and Arie basins in this area. The advance of glaciers during the LIA in the upper part of the basins led to the development of a braiding pattern and to channel aggradation corresponding to the highest glacifluvial levels. The decreasing activity of these braidplains occurred at the turn of the 19th and 20th centuries, immediately prior to a significant incision period. A second generation of braided channels developed during the first half of the 20th century. Ice‐marginal lake development, less input of fine‐grained sediment to the river channel, and fast incision began from the second half of the 20th century onward. During the last two decades, the main fluvial response to the climatic warming has been contraction of flow within a narrower channel and the abandonment of braidplains. The increased lateral erosion and rate of downcutting and the formation of the most downstream reaches of the modern valley bottom occurred in the 1980s and 1990s. This process was intensified under flood conditions generated by extreme rainfall events. These micro‐scale (small partially glaciated basins) observations concerning the changes of the activity of fluvial processes since the end of LIA may be helpful for the reconstruction of past fluvial changes over longer time scales.